2020
DOI: 10.3389/fnins.2020.583421
|View full text |Cite
|
Sign up to set email alerts
|

What’s That (Blue) Spot on my MRI? Multimodal Neuroimaging of the Locus Coeruleus in Neurodegenerative Disease

Abstract: The locus coeruleus (LC) has long been underappreciated for its role in the pathophysiology of Alzheimer’s disease (AD), Parkinson’s disease (PD), and other neurodegenerative disorders. While AD and PD are distinct in clinical presentation, both are characterized by prodromal protein aggregation in the LC, late-stage degeneration of the LC, and comorbid conditions indicative of LC dysfunction. Many of these early studies were limited to post-mortem histological techniques due to the LC’s small size and locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 220 publications
(267 reference statements)
2
32
1
Order By: Relevance
“…Our finding that structural disintegration of the LC is mostly present in the caudal part is in apparent contrast to post-mortem studies, which reported a uniform neuronal loss over the entire LC with PD and a preferential degeneration of rostral LC in Alzheimer's disease (44,45,(50)(51)(52). A post-mortem study in seven patients with PD and three healthy control cases found similar relative cell loss in rostral, middle and caudal LC sections ( 45), yet the greatest absolute cell loss was noted in the middle section.…”
Section: Spatial Gradient Of Signal Loss In the Locus Coeruleuscontrasting
confidence: 99%
“…Our finding that structural disintegration of the LC is mostly present in the caudal part is in apparent contrast to post-mortem studies, which reported a uniform neuronal loss over the entire LC with PD and a preferential degeneration of rostral LC in Alzheimer's disease (44,45,(50)(51)(52). A post-mortem study in seven patients with PD and three healthy control cases found similar relative cell loss in rostral, middle and caudal LC sections ( 45), yet the greatest absolute cell loss was noted in the middle section.…”
Section: Spatial Gradient Of Signal Loss In the Locus Coeruleuscontrasting
confidence: 99%
“…This supports a previously theorized buffering role of the LC, due to its high lifetime noradrenergic turnover and neuronal density, in protecting against the detrimental effects of accumulating AD-related pathology (Clewett et al 2015;Robertson 2013). Although the exact role of brainstem degeneration in cognitive dysfunction is not wellunderstood, degeneration of the LC appears to be related to cognitive function in normal aging (Dahl et al 2019;Langley et al 2020) and correlates with cognitive abilities and pathological protein accumulation in animal models of AD (Chalermpalanupap et al 2017;James et al 2020;Kelberman et al 2020). Of note, we found attenuated brainbehavior relationships in the biomarker-confirmed MCI due to AD group compared to the overall MCI group, likely due to the smaller sample size.…”
Section: Discussionsupporting
confidence: 82%
“…74 Based on such mechanistic insights, it will be interesting to probe whether the enhanced appearance of cyclic alternating patterns in cases of sleep-related breathing disorders, such as sleep apnea, can be controlled with noradrenergic antagonists. 54 Furthermore, there is strong evidence that LC and sleep disruptions could be linked in post-traumatic stress disorders; 18 in neurodegenerative diseases, such as Alzheimer's and Parkinson's disease; 75 and in insomnia. 5 We are now able to concretize questions into possible noradrenergic origins of a large variety of primary and secondary sleep disorders, in which hyperarousals, autonomic arousals, and movement-related arousals prominently feature.…”
Section: The Cellular and Ionic Mechanisms Underlying Noradrenergic Control Of Sleep-spindle Clusteringmentioning
confidence: 99%